Kebijakan Pengembangan Pendidikan Al-Qur’an di Kabupaten Pasuruan - Salahuddin, Rahmad (Universitas Muhammadiyah Sidoarjo, 2013)
The aim of this research was to describe the map of potential Al-Quran education in pasuruan and the development efforts have been conducted by the ministry of religion in improving services and governance of the implementation of Al-Quran education in the area. The method of this research used qualitative research. Based on this research showed that development of Al-Quran education in line with the vision of national development that puts the strategic role ofeducation, as stipulated in the constitution of 1945, namely to increase faith and devotion to the lord almighty, as well as noble morals of the people in order to educate, by means of ensuring fair distribution of educational opportunity as well as improving quality, relevance, and efficiency of the management of education in facing the local,, national, and global challenges.